MOKATAKE: BUDAYA MEGALITIK Dl SITUS HITIGIMA LEMBAH BALIM SELATAN KABUPATEN JAYAWIJAYA [MokatAke: Megalithic Culture in Hitigima] - Erlin Novita Icfje Ojami (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2016)
The findings of the spirits path or MokatAke in the Hltiglma Site, Asotlpo District, regency of Jayawijaya, has brought a new perspective related to the distribution and diversity of megalithb culture In Indonesia, in addition, as a proof that in the central mountainous region of Papua have also been touched by the megalithic culture, is a cultural tradition that was introduced byAustmnesian speakers since the Neolithic and continues a tradition until now. Research resuits from the Hitigima site is in the form ofAsama Indigenous Village, spirits path (mokat ake), a few of stone pillars, a large stone, and a niche in the mountain Hesagenem, as well as blue lake. These elements constitute a single entity associated with the context of indigenous deaths in Hubula tribe in southern Balim Valley, which is also described how the ancestors of the trip, and the reintegration of descent with ancestors. AbstrakTemuan jaian arwah atau mokat ake di Situs Hitigima, Distrik Asotlpo, Kabupaten Jayawijaya, telah msmbawa perspektif baru terkait dsngan sebaran dan keragaman bentuk megalitik di Indonesia. Di samping itu, sebagai bukti bahwa di wilayah pegunungan tengah Papua juga teiah tersentuh oleh budaya megalitik yaitu suaiu tradisl budaya yang diperkenalkan oleh penutur Austronesia sejak masa neolitik dan terns mentradisi hingga kini. Hasil penelltian di Situs Hitigima adalah berupa Kampung Adat Asoma, jaian arwah {mokat ake), beberapa buah tiang batu, satu buah batu berukuran besar, dan ceruk di Gunung Hesagenem, serta Kali Biru. Unsur-unsur tersebut merupakan satu kesatuan kontefcs yang terkait dengan adat kematian pada suku Hubuia di Lembah Balim selatan, yang juga menggambarkan tentang hubungan peijalanan nenek moyang, dan penyatuan kembali para ksturunan dengan ieluhumya.